2021
DOI: 10.3390/microbiolres12040070
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Optimization of Culture Conditions of a Bioflocculant-Producing Fungi from Kombucha Tea SCOBY

Abstract: Biolocculants are gaining attention in research due to their environmental friendliness and innocuousness to human in comparison to the conventional flocculants. The present study aimed to investigate the ability of fungi from Kombucha tea SCOBY to produce effective bioflocculant in bulk. A 16S rRNA gene sequence analysis was utilized to identify the isolate. The medium composition (carbon and nitrogen sources) and culture conditions (inoculum size, temperature, shaking speed, pH, and time) were optimized usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…This implies that carbohydrates are the most active components during the flocculation process. Moreover, the high carbohydrate content affirmed our previous study that the bioflocculant is thermally stable [ 24 ]. Bioflocculants dominated by protein content are known to be heat sensitive as proteins denature easily at high temperatures [ 47 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This implies that carbohydrates are the most active components during the flocculation process. Moreover, the high carbohydrate content affirmed our previous study that the bioflocculant is thermally stable [ 24 ]. Bioflocculants dominated by protein content are known to be heat sensitive as proteins denature easily at high temperatures [ 47 ].…”
Section: Resultssupporting
confidence: 84%
“…In our previous study, we isolated, identified and optimized culture conditions for a bioflocculant producing Pichia kudriavzevii MH545928.1 from Kombucha tea SCOBY [ 24 ]. Pichia kudriavzevii is the teleomorph of the Candida krusei that was previously regarded as Issatchenkia orientali .…”
Section: Introductionmentioning
confidence: 99%
“…About 50 mL of the medium was poured into different test tubes and autoclaved at 121 °C for 15 min. A loopful of the isolates was inoculated into the activation broth and incubated in a rotary shaker at 160 rpm, 37 °C for 24 h [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inoculum size greater than 1% led to the decrease in flocculating activity. The decrease might have been due to the extreme niche overlap of B. subtilis CSM5, which might have resulted in the inhibition of the bioflocculant production [28]. Generally, the inoculum sizes that fall within the range of 1 to 5% are of economic preferences [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, 2 mL of the culture broth was drawn every 12 h up to 96 h. The samples were then centrifuged at 12,000 rpm for 16 min. The supernatant was then used to evaluate the flocculating activity as previously described (see Section 2.2) [28].…”
Section: Optimization Of the Medium Composition And Culture Conditionsmentioning
confidence: 99%